Paradoxical CD4 Lymphopenia in Autoimmune Lymphoproliferative Syndrome (ALPS) - Lisco, Andrea; Wong, Chun-Shu; Price, Susan; Ye, Peiying; Niemela, Julie; Anderson, Megan; Richards, Elizabeth; Manion, Maura; Mystakelis, Harry; Similuk, Morgan; Lo, Bernice; Stoddard, Jennifer; et al. (Frontiers in Immunology, 2019)
Autoimmune lymphoproliferative syndrome (ALPS) is caused by germline or somatic loss of function FAS mutations resulting in impaired apoptosis and consequent expansion of T-lymphocytes causing organomegaly and autoimmune anemia, neutropenia and thrombocytopenia. Herein, we report on a case of disseminated varicella zoster infection after post-partum vaccination in a patient found to have CD4 lymphopenia and eventually diagnosed with ALPS caused by a novel germline missense mutation in FAS death-domain. A subsequent retrospective analysis of 169 patients of the NIH ALPS-FAS cohort, revealed that CD4-T-cells lymphopenia (<300 cells/μl) may occur in 5% of ALPS-FAS patients irrespectively of the underlying genetic defect, organomegaly or immunosuppressive treatment. Although immunophenotyping did not show depletion of specific CD4-T-cells subpopulations, CD4-lymphopenic ALPS-FAS subjects had an expansion of a subset of circulating T-follicular-helper (cTfh) cells, associated with autoantibody production (CCR7lowPD-1high). Furthermore, autoantibodies binding on CD4-T-cells were detected in 50% of the CD4-lymphopenic ALPS-FAS patients and caused cytotoxicity in a natural killer (NK)-mediated antibody-dependent-cellular cytotoxicity assay. Such autoantibodies can therefore be associated with CD4-T-cell death, impaired activation induced proliferation or impaired trafficking. The expansion of autoreactive T-cells in ALPS-FAS is known to be associated with autoimmune clinical manifestations, however our study reveals that ALPS-FAS can also be associated with a paradoxical depletion of CD4-T-cells due to the presence of autoantibodies on the surface of CD4-T-cells which can in turn result in increased susceptibility to opportunistic infections. These novel findings have implications for the diagnosis, clinical monitoring and management of patients with ALPS-FAS.